Pengaruh Kinerja Produk, Tingkat Kepuasan, dan Tingkat Keterlibatan pada Perilaku Perpindahan Merek - Pranita, Andina Jathu; Irawanto, Dodi W. (Universitas Brawijaya, Indonesia, 2013)
This study analyzed the effect of product performance, level of satisfaction, and level of involvement on brand switching behavior of mobile cards. Phenomena today shows that young people who often do brand switching behavior of mobile cards. The population in this study were all undergraduate students of Brawijaya University and obtained a sample of 100 college students who had been divided into a number of respondents for each faculty at Brawijaya University. Respondents in this study were students who have had experience in conducting brand switching cellular card and today still use one mobile card. Analysis tool used in this study is path analysis. Results showed several findings, the first is product performance affect the level of satisfaction. Second, the level of satisfaction can not mediate the effect of product performance on brand switching behavior. Third, product performance affect on brand switching behavior. Fourth, the level of involvement affect on brand switching behavior. Fifth, the level of involvement can not mediate the effect of product performance on brand switching behavior.